2022
DOI: 10.18388/abp.2020_5769
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of osteosarcoma cell proliferation in vitro and tumor growth in vivo in mice model by alstonine through AMPK-activation and PGC-1α/TFAM up-regulation

Abstract: Osteosarcoma, a leading malignant tumor of bones is diagnosed mostly in adolescents and young adults worldwide. The present study investigated alstonine as anti-osteosarcoma agent in vitro as well as in vivo and evaluated the underlying mechanism. Treatment with alstonine led to a significant (P<0.05) reduction in MG63 and U-2OS cell viability. Alstonine treatment of MG63 and U-2OS cells caused a significant reduction in colony formation compared to the control cells. Viability of osteoblasts was not affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…We first examined the gene and/or protein expression levels of Pgc1a and Tfam, as important factors of mitochondrial biogenesis in bone cells [24]. It is known that the AMPK/PGC1α axis is activated during osteoblast differentiation in C3H10T1/2 and Tfam is also up-regulated in osteoblast-like MG63 osteosarcoma cells [55,56]. On the other hand, osteoblast-specific Sod2 deficient mice develop an osteoporotic phenotype [21], while Nox2 increase leads to osteocyte apoptosis [57] and glucocorticoid-induced pre-osteoblast death [58] (41).…”
Section: Discussionmentioning
confidence: 99%
“…We first examined the gene and/or protein expression levels of Pgc1a and Tfam, as important factors of mitochondrial biogenesis in bone cells [24]. It is known that the AMPK/PGC1α axis is activated during osteoblast differentiation in C3H10T1/2 and Tfam is also up-regulated in osteoblast-like MG63 osteosarcoma cells [55,56]. On the other hand, osteoblast-specific Sod2 deficient mice develop an osteoporotic phenotype [21], while Nox2 increase leads to osteocyte apoptosis [57] and glucocorticoid-induced pre-osteoblast death [58] (41).…”
Section: Discussionmentioning
confidence: 99%
“…We first examined the gene and/or protein expression levels of Pgc1a and Tfam, important factors of mitochondrial biogenesis in bone cells [24]. It is known that the AMPK/PGC1α axis is activated during osteoblast differentiation in C3H10T1/2, and Tfam is also up-regulated in osteoblast-like MG63 osteosarcoma cells [75,76]. However, we found that Pgc1a was reduced on day 14 compared to day 7 in most of the conditions, suggesting a suppression of mitochondrial activity on a transcriptional level, which was not accompanied by the respective protein levels.…”
Section: Discussionmentioning
confidence: 99%